Earliest evidence of Neanderthal multifunctional bone tool production from cave lion (Panthera spelaea) remains - Grégory Abrams; Patrick Auguste; Stéphane Pirson; Isabelle De Groote; Éva Halbrucker; Kévin Di Modica; Camille Pironneau; Tristan Dedrie; Carlo Meloro; Valentin Fischer; Hervé Bocherens; Yves Vanbrabant; et al. (Scientific Reports)
Abstract Throughout history, humans have had a complex relationship with lions, both reverencing and fearing them. Interactions between Neanderthals and cave lions (Panthera spelaea) remain poorly documented due to the scarcity of direct evidence. This study examines the selective use of cave lion bones by Neanderthals to determine whether this behaviour was driven by practical, functional, or symbolic factors, through a detailed zooarchaeological analysis. Previous studies highlighted Neanderthals’ skinning and butchering of cave lions, yet new discoveries at Scladina Cave (Belgium) offer deeper insights into this relationship. Dated to the end of the Saalian, the faunal assemblage provides the earliest evidence of bone tools crafted from cave lion remains. A tibia was deliberately processed into multifunctional tools, initially serving as an intermediate tool before being repurposed as retouchers. Proteomic analysis applied on the remains, confirmed the specific identification. These findings reveal that Neanderthals not only competed with but actively utilized cave lions for practical purposes, indicating complex ecological and behavioral interactions. Relationships between pre-humans and large predators, rooted in the Middle Pleistocene, suggest a strategic exploitation of carnivore remains. However, opportunistic procurement cannot be entirely ruled out as a potential factor influencing animal choice in tool production. The intentional transformation of lion bones into functional tools highlights Neanderthals’ cognitive skills, adaptability, and capacity for resource utilization beyond their immediate survival needs.